Asymmetric [4+2] Annulation of C1 Ammonium Enolates with Copper‐Allenylidenes. Issue 19 (31st March 2017) - Song, Jin; Zhang, Zi‐Jing; Gong, Liu‐Zhu
Abstract: An asymmetric catalytic decarboxylative [4+2] annulation of 4‐ethynyl dihydrobenzooxazinones and carboxylic acids has been established by cooperative copper and nucleophilic Lewis base catalysis. A C1 ammonium enolate and copper–allenylidene complex, each catalytically generated from different substrates, underwent a cascade asymmetric propargylation and lactamization process to yield optically active 3, 4‐dihydroquinolin‐2‐one derivatives with excellent levels of stereoselectivity (up to 99 % ee, 95:5 d.r.). Abstract : A team effort : An asymmetric [4+2] annulation of C1 ammonium enolates with copper–allenylidenes catalytically generated from carboxylic acids and 4‐ethynyl dihydrobenzooxazinones, respectively, led to optically active 3, 4‐dihydroquinolin‐2‐one derivatives with excellent levels of stereoselectivity.